2020
DOI: 10.1111/anu.13149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vegetable oil on growth performance, digestive capacity, antioxidant capacity and expression of immune‐related genes in the hybrid grouper (Epinephelus fuscoguttatus♀ ×E. lanceolatus♂)

Abstract: An 8-week feeding experiment was conducted to investigate the effects of dietary lipid sources on growth performance, digestive capacity, antioxidant capacity and expression of immune-related genes in the hybrid grouper (Epinephelus fuscoguttatus ♀× E. lanceolatus ♂). Five isoproteic and isolipidic experimental diets were formulated containing fish oil (FO), soybean oil (SO), linseed oil (LO), rapeseed oil (RO) and peanut oil (PO), respectively. Results showed that fish fed the FO diet had the highest weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…The current study reported that L. crocea fed the diet with 100% LO had lower CAT activity and a higher concentration of MDA than the control group. Similar effects were found in Japanese seabass ( Lateolabrax japonicus ) ( Tan et al, 2017 ) and hybrid grouper ( Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) ( An et al, 2020 ). ALA has been confirmed to increase mitochondrial DNA methylation in the liver, which can induce oxidative stress in fish ( Liao et al, 2015 ).…”
Section: Discussionsupporting
confidence: 66%
“…The current study reported that L. crocea fed the diet with 100% LO had lower CAT activity and a higher concentration of MDA than the control group. Similar effects were found in Japanese seabass ( Lateolabrax japonicus ) ( Tan et al, 2017 ) and hybrid grouper ( Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) ( An et al, 2020 ). ALA has been confirmed to increase mitochondrial DNA methylation in the liver, which can induce oxidative stress in fish ( Liao et al, 2015 ).…”
Section: Discussionsupporting
confidence: 66%
“…Similar to other cultured marine fish species, fish oil is the primary lipid source for hybrid groupers. Considering the non-sustainable reliance on fish oil to farm this species, several trials have investigated the impact of the dietary replacement of fish oil with alternatives [30][31][32][33]. However, studies related to the molecular basis of LC-PUFA biosynthesis and regulation, which could optimize the pathway to the efficient use of alternatives, are still limited in hybrid groupers.…”
Section: Discussionmentioning
confidence: 99%
“…The desaturation and elongation capacity varies with the fish species (Monroig et al, 2011). The effects of the incorporation of dietary VOs in aquaculture feeds have been previously worked out in many fish species, such as Psetta maxima (Regost et al, 2003), European sea bass, Dicentrarchus labrax (Mourente et al, 2005), rohu, Labeo rohita (Karanth et al, 2009), iridescent shark, Pangasius hypophthalmusturbot (Asdari et al, 2011), blunt snout bream, Megalobrama amblycephala (Li et al, 2015), gibel carp, Carassius auratus gibelio (Zhou et al, 2016), hybrid grouper, Epinephelus fuscoguttatus × E. lanceolatus (An et al, 2020), common carp, Cyprinus carpio (Ren et al, 2020), golden pompano, Trachinotus ovatus (Guo et al, 2021), turbot, Scophthalmus maximus (Xu et al, 2021), tiger puffer, Takifugu rubripes (Liao et al, 2021), and blackhead seabream, Acanthopagrus schlegelii (Zhu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%